Hydrostatic-pressure-induced changes of magnetic anisotropy in (Ga, Mn)As thin films. (7th February 2017) - Gryglas-Borysiewicz, Marta; Juszyński, Piotr; Kwiatkowski, Adam; Przybytek, Jacek; Sadowski, Janusz; Sawicki, Maciej; Tokarczyk, Mateusz; Kowalski, Grzegorz; Dietl, Tomasz; Wasik, Dariusz
Abstract: The impact of hydrostatic pressure on magnetic anisotropy energies in (Ga, Mn)As thin films with in-plane and out-of-plane magnetic easy axes predefined by epitaxial strain was investigated. In both types of sample we observed a clear increase in both in-plane and out-of-plane anisotropy parameters with pressure. The out-of-plane anisotropy constant is well reproduced by the mean-field p–d Zener model; however, the changes in uniaxial anisotropy are much larger than expected in the Mn–Mn dimer scenario.